Brown tumour as an unusual but preventable cause of spinal cord compression: case report and literature review - Banu, Sabiha; Furqan, Saira (Journal of the Pakistan Medical Association, 2023)
Brown tumour is an infrequent, focal, and benign osteolytic lesion which is a consequence of abnormal bone metabolism in hyperparathyroidism (both primary and secondary). It is also known as Osteoclastoma. In the present era, we rarely encounter skeletal disease caused by primary hyperparathyroidism. Although it is a rare presentation because of advancement of treatment but still can be encountered because of lack of standard care so we should have high index of suspicion to avoid this preventable complication. We report here a case of brown tumour in the thoracic vertebra of a young female patient with End Stage Renal Disease, who presented with backache and bilateral lower limb weakness. MRI of the spine showed multiple non-enhancing abnormal signals involving vertebral body of C2, posterior elements of C6, and bilateral sacral vertebra, suggestive of healed fractures versus bone forming tumours. She underwent laminectomy. ---Continue